Cover Picture: Alternately π‐Stacked Systems Assisted by o‐Carborane: Dual Excimer Emission and Color Modulation by Bcage‐Methylation (Angew. Chem. Int. Ed. 2/2023). Issue 2 (22nd December 2022) - Ochi, Junki; Tanaka, Kazuo; Chujo, Yoshiki
Abstract : Unique solid‐state emission from three types of acridine‐tethered boron clusters, o ‐carboranes, with variable degrees of methylation, is reported by Kazuo Tanaka et al. in their Research Article (e202214397 ). It is found that monomer emission, excimer emission from the π ‐stacked intra‐dimer unit, and excimer emission from the π ‐stacked inter‐dimer unit can be simultaneously obtained. Consequently, not only drastic luminescent color changes but also thermochromic luminescence properties were observed.